2011
DOI: 10.1177/1059601111402684
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Ownership in Small Family-Owned Businesses: Leadership Style and Nonfamily-Employees’ Work Attitudes and Behaviors

Abstract: Using a sample of 229 nonfamily employees working in 52 small family-owned businesses, we examined the relationships between owner-managers’ leadership style and employees’ psychological ownership of the family business and their job. We also examined whether psychological ownership mediated the link between leadership style and employees’ organizational attitudes and behaviors. Hierarchical linear modeling (HLM) analysis confirmed transformational and transactional leadership as contextual facilitators of psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
184
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(212 citation statements)
references
References 90 publications
5
184
0
13
Order By: Relevance
“…These four aspects -participative decision-making, distributive justice, succession planning and extra-role behaviours -are driven by either transactional or relational obligations between the family firm and its family-member employees. Each aspect can influence the psychological contract between family-member employees (Bernhard and O'Driscoll, 2011), ultimately resulting in impacts to the family firm's financial performance.…”
Section: Literature Review and Theoretical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These four aspects -participative decision-making, distributive justice, succession planning and extra-role behaviours -are driven by either transactional or relational obligations between the family firm and its family-member employees. Each aspect can influence the psychological contract between family-member employees (Bernhard and O'Driscoll, 2011), ultimately resulting in impacts to the family firm's financial performance.…”
Section: Literature Review and Theoretical Developmentmentioning
confidence: 99%
“…Although certain behaviours may be considered extra role by the employee and employer, they are nonetheless important to the performance of the primary tasks of the organisation (Organ, 1997;Pearce and Gregersen, 1991), and these extra-role behaviours contribute to the overall work environment, especially in the case of family firms where extrarole behaviours are associated with higher levels of involvement and identification (Bernhard and O'Driscoll, 2011). Within the framework of social exchange theory and psychological contracts, these behaviours constitute transactional obligations from the family-member employee towards the organisation, thus fulfilling this portion of the psychological contract.…”
Section: Extrarole Behaviourmentioning
confidence: 99%
“…However, Pierce and colleagues argue that feelings of ownership for a particular target will be strongest when all three routes are operating, and that control and investment of self in the target may be more potent than intimate knowledge. Very little empirical evidence is available regarding what the most effective routes may be, or ESO's potential to enhance a possession based definition of PO (those that have include Bernhard & O'Driscoll, 2011;Brown et al, 2013;Chi & Han, 2008;McCarthy & Palcic, 2012). Despite Pierce et al's (1991) theoretical work depicting a relationship between ESO and PO, no known study has explored with employees how they make sense of their ESO experiences and feelings of ownership.…”
Section: Eso and The Routes To Psychological Ownershipmentioning
confidence: 99%
“…Psychological ownership implies that individuals are psychologically intertwined and emotionally attached with their organization (Bernhard & O'Driscoll, 2011). Actually, the self and the target of possession are so interrelated to such an extent that it becomes difficult to separate them, so people may define themselves by possessions they own (Avey et al, 2009 Moreover, people develop a sense of Psychological ownership to fulfill several basic and important needs including sense of control, home (comfort and security), and self-identity.…”
Section: Workplace Bullying-psychological Ownershipmentioning
confidence: 99%
“…Lastly, we enumerate empirical results supporting the claim that workplace bullying can curtail the sense of psychological ownership. Bernhard and O'Driscoll, (2011) found that leaders behaviors exhibited toward their followers affect the employees' feeling of psychological ownership. Another study in different, but related field of study, found that fair treatment is related to organizational attachment (Haque & Asalm, 2011).…”
Section: Workplace Bullying-psychological Ownershipmentioning
confidence: 99%